Free methyl salicylate and its glycosides mapping in monovarietal Italian white wines - Maurizio Piergiovanni; Domenico Masuero; Silvia Carlin; Giovanni Luzzini; Nicole Furlan; Davide Slaghenaufi; Maurizio Ugliano; Luca Rolle; Susana Río Segade; Paola Piombino; Elisabetta Pittari; Andrea Versari; et al. (OENO One, 2023)
Aroma is an identifying characteristic of wines and is of crucial importance for the consumer appreciation. Among all odour-active compounds, some key molecules appear only after ageing and give a strong contribution to both identity and added value of the wine bottle. Methyl salicylate (MeSA) is an odorant which usually appears after ageing and could provide an increase in fruity aromas and freshness. This odour-active ester can be found mainly bound to one or more carbohydrates, forming a glycoside. In wines, the hydrolysis of glycosides contributes to the aroma evolution of wine. In our previous works, MeSA was found in relevant content, both in bound and free form, in some genetically related Italian varieties such as Trebbiano di Lugana, Trebbiano di Soave (both employed in the production of Lugana wines), and Verdicchio. In this research, a straightforward filter-and-shot LC-MS/MS method was used for the determination of 7 different MeSA glycosides in 246 samples representative of 18 different monovarietal Italian white wines. MeSA glycosides were found in relevant concentrations in Verdicchio and Lugana wines, whereas they were determined for the first time in all others. Results were in accordance with the literature since Lugana and Verdicchio emerged for the total amount of glycosides, together with Erbaluce, whose richness was not known to date. This trend was observed for all analytes, with stronger intensity, especially in MeSA–glucoside, MeSA–gentiobioside and MeSA–violutoside. The triglycosylated form was not detected in any case. The same trend was also observed for the free form, whose value was not above the olfactory threshold for any sample. MeSA in all its forms also showed a qualitative trend, with MeSA - glucoside and MeSA–primeveroside emphasised in richer cultivars with also a characteristic pattern. The knowledge of the concentration of MeSA glycosides could be considered a potential predictor of the potential evolution of white wines towards balsamic-like nuances.